Latino Residential Isolation and the Risk of Obesity in Utah: The Role of Neighborhood Socioeconomic, Built-Environmental, and Subcultural Context - Wen, Ming (2011)
The prevalence rate of obesity in the United States has been persistently high in recent decades, and disparities in obesity risks are routinely observed. Both individual and contextual factors should be considered when addressing health disparities. This study examines how Latino-white spatial segregation is associated with the risk of obesity for Latinos and whites, whether neighborhood socioeconomic resources, the built environment, and subcultural orientation serve as the underlying mechanisms, and whether neighborhood context helps explain obesity disparities across ethnic and immigrant groups. The study was based on an extensive database containing self-reported BMI measures obtained from driver license records in Utah merged with census data and several GIS-based data. Multilevel analyses were performed to examine the research questions. For both men and women, Latino residential isolation is significantly and positively linked to the risk of obesity; after controlling for immigrant concentration, this effect gets amplified. Moreover, for men and women, the segregation effect is partly attributable to neighborhood SES and the built environment; and only for women is it partly attributable to obesity prevalence in the neighborhood. Place matters for individual risk of obesity for both men and women and there are multifarious pathways linking residence to obesity. Among the demographic, socioeconomic, physical, and cultural aspects of neighborhood context examined in this study, perhaps the most modifiable environment features that could prevent weight gain and its associated problems would be the built environmental factors such as greenness, park access, and mixed land use.